2022
DOI: 10.1155/2022/8259927
|View full text |Cite
|
Sign up to set email alerts
|

TFPPASV: A Three-Factor Privacy Preserving Authentication Scheme for VANETs

Abstract: A vehicular ad hoc network (VANET) is essential for the autonomous vehicle industry, and with the advancement in VANET technology, security threats are increasing rapidly. Mitigation of these threats needs an intelligent security protocol that provides unbreakable security. In recent times, various three-factor authentication solutions for VANET were introduced that adopt the centralized Trusted Authority … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Xu et al [20] also presented a three-factor CPPA scheme in VANETs. Duan et al [21] demonstrated that Xu et al's [20] protocol is insecure; in the presence of an untrustworthy RSU, it has the ability to circumvent the Trusted Authority (TA) and establish a session key directly with the vehicle. To solve this issue, Duan et al [21] proposed an improved scheme.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Xu et al [20] also presented a three-factor CPPA scheme in VANETs. Duan et al [21] demonstrated that Xu et al's [20] protocol is insecure; in the presence of an untrustworthy RSU, it has the ability to circumvent the Trusted Authority (TA) and establish a session key directly with the vehicle. To solve this issue, Duan et al [21] proposed an improved scheme.…”
Section: Related Workmentioning
confidence: 99%
“…Duan et al [21] demonstrated that Xu et al's [20] protocol is insecure; in the presence of an untrustworthy RSU, it has the ability to circumvent the Trusted Authority (TA) and establish a session key directly with the vehicle. To solve this issue, Duan et al [21] proposed an improved scheme. However, Duan et al's [21] scheme lacks untraceable, known-session key secrecy and three-factor secrecy.…”
Section: Related Workmentioning
confidence: 99%
“…Efficiency With respect to Proposed scheme Amit [17] 8.20% less efficient Vangala (Case 1) [43] 28.97% less efficient Vangala (Case 2) [43] 29.96% less efficient Tan (V2RSU) [44] 213.85% less efficient Challa [45] 61.12% less efficient Anil Kumar [31] 44.11% less efficient Chen [46] 103.20% less efficient Palak (Case 1) [36] 2.77% more efficient Palak (Case 2) [36] 28.97% less efficient Cui [21] 92.78% less efficient Duan [47] 12.35% more efficient Zhang [48] 27.00% less efficient Vangala [34] 65.47% less efficient Sadhukhan [33] 28.8% less efficient…”
Section: Schemesmentioning
confidence: 99%
“…Amit [17] Vangala [43] Tan [44] Challa [45] Anil- [31] Cui- [21] Duan- [47] Zhang- [48] Fig. 2 Total computation cost related graph…”
Section: Security Requirementsmentioning
confidence: 99%
See 1 more Smart Citation